Longitudinal zonation of the benthic invertebrate fauna in the river Glomma, Eastern Norway - Albert Lillehammer; John E. Brittain (Fauna Norvegica)
Zonation studies of the benthic invertebrate fauna of stony substrates were made along a longitudinal gradient (600 km) in the Glomma river which drains 13% of Norway's land area (41767 km2). Wide differences in the faunal composition were found between the upper, middle and lower reaches of the river. Plecoptera were most abundant in the upper and Chironomidae and Trichoptera in the lower reaches. Ephemeroptera were abundant throughout the river. The faunal composition showed a dominance of shredders in the upper, grazers in the middle and collectors in the lower reaches. Some local effects of human influence were observed, but no general changes from the natural faunal composition and zonation seem to have taken place. The benthic data are in general agreement with the predictions of the River Continuum Concept (Vannote et al. 1980).